Courses
Courses for Kids
Free study material
Offline Centres
More
Store

# How do you find the intercepts of $2x + y = 6$?

Last updated date: 20th Jun 2024
Total views: 374.7k
Views today: 4.74k
Verified
374.7k+ views
Hint: Here we need to find x-intercept and y-intercept. We know that x-intercept is a point on the graph where ‘y’ is zero.
Also we know that y-intercept is a point on the graph where ‘x’ is zero. In other words the value of ‘x’ at ‘y’ is equal to zero is called x-intercept. The value of ‘y’ at ‘x’ is equal to zero is called t-intercept. Using this definition we can solve the given problem.

Complete step by step solution:
Given,
$2x + y = 6$.
To find the x-intercept we substitute $y = 0$ in the given equation we have,
$2x + (0) = 6$
$2x = 6$
Dividing by 2 on both side of the equation we have
$x = \dfrac{6}{2}$
$x = 3$
That is x-intercept is 3.
To find the y-intercept we substitute $x = 0$ in the given equation we have,
$2(0) + y = 6$
$y = 6$
That is y-intercept is 6.
Thus, we have the x-intercept is 3. The y-intercept is 6.

Note: We can also solve this by converting the given equation into the equation of straight line intercept form. That is $\dfrac{x}{a} + \dfrac{y}{b} = 1$. Where ‘a’ is a x-intercept and ‘b’ is called y-intercept.
Now given,
$2x + y = 6$
We need 1 on the right hand side of the equation. So we divide the equation by 6 on both sides.
$\dfrac{{2x + y}}{6} = \dfrac{6}{6}$
Separating the terms in the left hand side of the equation. We have,
$\dfrac{{2x}}{6} + \dfrac{y}{6} = \dfrac{6}{6}$
Now cancelling we have,
$\dfrac{x}{3} + \dfrac{y}{6} = 1$.
Now comparing with the standard intercept equation we have,
The x-intercept is 4. The y-intercept is 3. In both the methods we have the same answer. We can choose any one method to solve this.